2017
DOI: 10.1002/pbc.26873
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pediatric patients with acute lymphoblastic leukemia/lymphoblastic lymphoma with hypersensitivity to pegaspargase treated with PEGylated Erwinia asparaginase, pegcrisantaspase: A report from the Children's Oncology Group

Abstract: Background Erwinia asparaginase is a Food and Drug Administration approved agent for the treatment of acute lymphoblastic leukemia (ALL) for patients who develop hypersensitivity to Escherichia coli derived asparaginases. Erwinia asparaginase is efficacious, but has a short half-life, requiring six doses to replace one dose of the most commonly used first-line asparaginase, pegaspargase, a polyethylene glycol (PEG) conjugated E. coli asparaginase. Pegcristantaspase, a recombinant PEGylated Erwinia asparaginase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
43
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 40 publications
(92 reference statements)
0
43
0
3
Order By: Relevance
“…PEG was long considered to be nonimmunogenic, but recent reports show that anti-PEG antibodies can be induced by injection of some types of pegylated liposomes or proteins in clinical trials [6][7][8][9][10][11][12][13][14] and animal studies [15][16][17][18][19][20][21][22][23][24]. Although anti-PEG antibodies do not appear to be induced when most pegylated human proteins are administered to patients, a large proportion of the general population never exposed to pegylated drugs has pre-existing anti-PEG antibodies in their circulation, possibly due to widespread exposure to PEG in commonly used products such as cosmetics, soaps, and medicines [10][11][12]16,[25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG was long considered to be nonimmunogenic, but recent reports show that anti-PEG antibodies can be induced by injection of some types of pegylated liposomes or proteins in clinical trials [6][7][8][9][10][11][12][13][14] and animal studies [15][16][17][18][19][20][21][22][23][24]. Although anti-PEG antibodies do not appear to be induced when most pegylated human proteins are administered to patients, a large proportion of the general population never exposed to pegylated drugs has pre-existing anti-PEG antibodies in their circulation, possibly due to widespread exposure to PEG in commonly used products such as cosmetics, soaps, and medicines [10][11][12]16,[25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-PEG antibodies can bind and accelerate the clearance of pegylated enzymes, proteins, and nanocarriers conjugated with multiple PEG chains in animals ( Table 2) [18][19][20][21][22][23][32][33][34][35][36]. High levels of induced anti-PEG antibodies can also alter the half-life and biological activity of pegylated drugs in patients [7,8,11,14]. Pre-existing anti-PEG antibodies have also been linked to allergic reactions after the infusion of pegylated medicines [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…A Phase I study of this agent was successfully conducted in 10 adults aged 18–50 years (median, 40.6 years) without a previous history of allergic reaction to Erwinase; few if any of these patients would have been previously exposed to pegaspargase, a drug seldom used to treat adults with ALL, especially before native asparaginase was discontinued in the United States in December 2012. In this issue of Pediatric Blood & Cancer , Rau et al . from the Children's Oncology Group reported the results of a Phase II trial of intravenous pegcrisantaspase in pediatric patients with ALL or lymphoblastic lymphoma who had a history of grade 2 or more hypersensitivity reactions to pegaspargase.…”
mentioning
confidence: 99%
“…As mentioned by Rau and colleagues, PEG has been used not only in the pharmaceutical industry but also in processed foods and cosmetics. Although PEG has been considered poorly immunogenic over the years, multiple recent studies have shown that anti‐PEG IgG and IgM can be detected at low levels in approximately 70% and at high levels in up to 7% of the general population, leading to serious reactions upon first exposure to PEGylated medicines .…”
mentioning
confidence: 99%
See 1 more Smart Citation